Attention-driven scenography - Skarth-Hayley, Luke (2025)
Game engines now find use beyond video games for virtual production in television, film, and other fields. Streaming services also use these engines to provide games and interactive media for new audiences. While interactive media become more accessible via these technologies, game engines still hold novel narrative design opportunities. They offer significant possibilities in the production of interactive narrative experiences in rich virtual environments. Interactive and adaptive narrative spaces can enhance immersion and provide experiences other media do not. Yet branching narrative remains a common design pattern.